Atherogenic cytokines and chemokines in chronic hepatitis C are not associated with the presence of cardiovascular diseases. (March 2019) - Santos, Taciana Pereira Sant'Ana; Pereira, Mariana de Menezes; Schinoni, Maria Isabel; Sampaio, Geraldo Pedral; Aras, Roque; Atta, Maria Luiza Sousa; Atta, Ajax M.
Highlights: Chronic hepatitis C was associated with insulin resistance without diabetes. The production of GDF-15 was elevated in CHC patients. Increased production of atherogenic cytokines was observed in PBMC. No increase in atherogenic risk indexes and frequency of prior myocardial infarction. Abstract: There appears to be an associative link between chronic hepatitis C (CHC) and cardiovascular diseases (CVDs). However, the exact nature of the relationship between CHC and CVDs has not been elucidated. We investigated the presence of CVDs and the clinical and laboratory alterations associated with these diseases in CHC patients. Twenty-six CHC patients, 35 individuals with atherosclerosis (Athero) and 27 healthy individuals were examined for risk factors for CVD, lipid profile, atherogenic risk indexes, and insulin resistance (IR). Cardiac biomarkers and the chemokines and cytokines involved in atherosclerosis were also evaluated. A higher prevalence of prior acute myocardial infarction was found in the Athero group. Most CHC patients were infected with the hepatitis C virus genotype 1 and exhibited either no hepatic fibrosis or a mild to moderate liver fibrosis. The apolipoprotein B/apolipoprotein A-I and triglyceride/high-density lipoprotein cholesterol ratios and C-reactive protein levels were lower in CHC patients than in the Athero group. Further, IR was elevated in the CHC group and associated with the waist circumference. High GDF-15 levels were observed in the CHC group, which were inversely correlated with APOB levels. Peripheral blood mononuclear cells from CHC patients produced more IFN-γ, TNF-α and IL-6 than CAD PBMC but the production of IL-10 and IL-1β was similar. CHC and CAD groups presented similar levels of IL-8, MCP-1 and LAP-TGF-β1. Increased IR, elevated levels of GDF-15, and high production of atherogenic cytokines can be observed in Brazilian CHC patients without association with diabetes and clinical manifestation of cardiovascular diseases.